2012
DOI: 10.1177/016264341202700203
|View full text |Cite
|
Sign up to set email alerts
|

Support Needs of Adults with Intellectual Disability across Domains: The Role of Technology

Abstract: People with and without disabilities universally value the goals of greater control and self-determination, inclusion and participation in their school or community, and enhanced social inclusion. Technology is an important support in achieving these goals. In this manuscript we examine the intensity of support needs, as measured by the Supports Intensity Scale, of persons with intellectual disability (ID) by severity of their intellectual deficit, as well as examining the level of support needs of individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
1
30
0
2
Order By: Relevance
“…Wehmeyer et al (2012) found that their participants with physical disabilities scored higher in 'Home Living', 'Community Living' and 'Health and Safety'. This finding is consistent with those obtained in adult populations.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Wehmeyer et al (2012) found that their participants with physical disabilities scored higher in 'Home Living', 'Community Living' and 'Health and Safety'. This finding is consistent with those obtained in adult populations.…”
Section: Discussionmentioning
confidence: 91%
“…Once the suitability of SIS-C for measuring the support needs of children with IMD has been verified, the second objective would be to investigate the impact of IMD on support needs by comparing children with and without IMD in each SIS-C dimension. We expected children with motor and cognitive impairments to have greater support needs than children with ID alone, especially in areas related to mobility and participation in home and community settings (Palisano et al 2003;Wehmeyer et al 2012;Heineman et al 2018). Moreover, ID levels were expected to have some effect on the comparisons (Thompson et al 2009), with less significant differences in support needs among children with severe or profound ID (which is also evidence of criterion validity).…”
Section: Objectives Of the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Technology can promote greater independence by increasing access to information, supporting social interactions and enhancing endurance or ability to complete tasks that might otherwise be too difficult (Owuor et al 2017). In addition, technology use can enhance an individual's sense of control, self-determination and inclusion (Wehmeyer et al 2012b). Improved outcomes also include literacy; vocational, transition and employment skills; living skills; and communication (Lancioni et al 1999;Standen et al 2001;Davies et al 2002;Hetzroni et al 2002;Standen and Brown 2005;Tam et al 2005;Schlosser and Sigafoos 2006;Stock et al 2006;Wilkinson and Hennig 2007;Davies et al 2008;Wehmeyer et al 2008;Stock et al 2011).…”
Section: Technology Use Among Individuals With Intellectual and Develmentioning
confidence: 99%
“…In addition, technology use can enhance an individual's sense of control, self‐determination and inclusion (Wehmeyer et al . ). Improved outcomes also include literacy; vocational, transition and employment skills; living skills; and communication (Lancioni et al .…”
Section: Introductionmentioning
confidence: 97%